Cytotoxic effect of the ethanolic extract of Calotropis procera flowers on human cancer cell lines - Alryahi, Israa Abd; Mohammed, Fadia Hameed; N. Al-Saily, Hala M. (Pharmakeftiki, 2025)
Conventional cancer treatments are often associated with adverse effects, prompting researchers to investigate alternative anticancer agents deriving from natural sources, including traditional medicinal plants. One such plant, Calotropis procera L., is rich in phytochemicals with broad pharmacological potential. This study has evaluated the cytotoxic effects of its flower’s extract on two cancer cell lines – human osteosarcoma (MG63) and human glioblastoma (A172) – using normal human dermal fibroblasts (neonatal; HdFn) as a control. The MTT assay was employed in order to assess cytotoxicity and apoptosis induction. Our results demonstrate a dose-dependent inhibition of cell growth. The most effective concentrations of the Calotropis procera flower extract were 400, 200, and 100 µg/mL, with MG63 cells showing greater sensitivity than A172 cells. No cytotoxicity was observed in HdFn cells. The IC50 values were 213.7 µg/mL for MG63, 282.66 µg/mL for A172, and 844.08 µg/mL for HdFn. The selective cytotoxicity of the extract is attributed to the presence of potent phytochemicals that induce apoptosis in cancer cells without harming healthy cells. These findings suggest that the flower extract of Calotropis procera may serve as a promising and safe anticancer agent.